Baseline perihematomal edema, C-reactive protein, and 30-day mortality are not associated in intracerebral hemorrhage - Sobowale, Oluwaseun A.; Hostettler, Isabel C.; Wu, Teddy Y.; Heal, Calvin; Wilson, Duncan; Shah, Darshan G.; Strbian, Daniel; Putaala, Jukka; Tatlisumak, Turgut; Vail, Andy; Sharma, Gagan; Davis, Stephen M.; et al. (Frontiers in Neurology, 2024)
The relationship between baseline perihematomal edema (PHE) and inflammation, and their impact on survival after intracerebral hemorrhage (ICH) are not well understood.Objective: Assess the association between baseline PHE, baseline C-reactive protein (CRP), and early death after ICH.Methods: Analysis of pooled data from multicenter ICH registries. We included patients presenting within 24 hours of symptom onset, using multifactorial linear regression model to assess the association between CRP and edema extension distance (EED), and a multifactorial Cox regression model to assess the association between CRP, PHE volume and 30-day mortality.We included 1034 patients. Median age was 69 (interquartile range [IQR] 59-79), median baseline ICH volume 11.5 (IQR 4.3-28.9) mL, and median baseline CRP 2.5 (IQR 1.5-7.0) mg/L. In the multifactorial analysis (adjusting for cohort, age, sex, log-ICH volume, ICH location, intraventricular hemorrhage (IVH), statin use, glucose and systolic blood pressure), baseline log-CRP was not associated with baseline EED: for a 50% increase in CRP the difference in expected mean EED was 0.004 cm (95%CI 0.000 to 0.008, p=0.055). In a further multifactorial analysis, after adjusting for key predictors of mortality, neither a 50% increase in PHE volume nor CRP were associated with higher 30-day mortality (HR 0.97; 95%CI 0.90 to 1.05, p=0.51 and HR 0.98; 95%CI 0.93 to 1.03, p=0.41, respectively).Higher baseline CRP is not associated with higher baseline edema, which is also not associated with mortality. Edema at baseline might be driven by different pathophysiological processes with different effects on outcome.